Research on the Asset Liability Management Mechanism of Commercial Banks Taking Silicon Valley Bank as an Example - Jian, Yangyang; Liang, Keke; Sun, Yifei; Zhang, Fan (LPPM STIKI Malang, 2024)
Since 2023, the bank bankruptcy incidents in the United States, represented by Silicon Valley Bank, have continued to ferment, causing bank runs and capital market turmoil, and spreading panic in the financial market. This article takes Silicon Valley Bank as an example to review the beginning and end of the bankruptcy event caused by the liquidity crisis, and analyzes the reasons for its bankruptcy from internal factors such as bank asset liability maturity mismatch, weakened capital adequacy ratio, and lack of risk management measures, as well as external environmental factors such as the Federal Reserve's aggressive interest rate hike and the cold winter of Silicon Valley technology industry, On this basis, suggestions are proposed for optimizing asset liability structure management and strengthening risk warning and regulatory mechanisms in China's banking industry risk management. Based on the strategic orientation of promoting high-quality development of the financial industry in China, this article provides industry insights from the analysis of the bankruptcy events of Silicon Valley banks, which has certain practical value for strengthening risk management and supervision of banking institutions in China.